Emerging Function and Clinical Significance of Exosomal circRNAs in Cancer - Man Wang; Fei Yu; Peifeng Li; Kun Wang (Elsevier, 2020)
Exosomes are a type of extracellular vesicles (EVs) secreted by almost all cells, with a diameter range of 30-150 nm and a lipid bilayer membrane. Exosomes are now considered as vital mediators of intercellular communication and participate in multiple cellular processes, such as signal transduction and antigen presentation. Recently, circular RNAs (circRNAs), a novel class of noncoding RNAs (ncRNAs), have been found to be abundant and stable in exosomes. Increasing evidence indicates that exosome-derived circRNAs act as signaling molecules to regulate cancer growth, angiogenesis, invasion, metastasis, and sensitivity to chemotherapy. Moreover, circulating exosomal circRNAs can reflect the progression and malignant characteristics of cancer, implying their great potential as promising, non-invasive biomarkers for cancer diagnosis and prognosis. In this review, we summarize the recent progress on the functional roles of exosomal circRNAs in cancer progression, discussing their potential as promising biomarkers and therapeutic targets in cancer. Comprehensive elucidation of molecular mechanisms relevant to the implications of exosomal circRNAs in cancer progression will be conducive to the development of innovative diagnostic and therapeutic approaches in cancer.